Clonal spread of methicillin-resistant Staphylococcus aureus-t6065-CC5-SCCmecV-agrII in a Libyan hospital. (September 2017) - Khemiri, Monia; Akrout Alhusain, Ali; Abbassi, Mohamed Salah; El Ghaieb, Houyem; Santos Costa, Sofia; Belas, Adriana; Pomba, Constança; Hammami, Salah
Highlights: 32 MRSA isolates recovered from wound specimens in Hospital from Tripoli, Lybia, were studied. Isolates were clonal and belonged to CC5, harboured the SCCmecV element, the spa type was t6065, and harboured the agrII . Isolates were multidrug-resistant and exfoliative-, enterotoxin-, haemolysin- encoding genes and immune evasion cluster proteins were relevant. This is the first report of a specific clonal spread of a multi-drug resistant MRSA-CC5-SCCmecV in Libyan Hospital. Abstract: Objectives: The aim of this study was to characterize 32 MRSA isolates recovered from wound specimens of patients in a Hospital in Tripoli, Libya, during 2013. Methods: MRSA isolates were characterized by determining their antibiotic susceptibilities, genes encoding antibiotic resistance and virulence factors, the SCC mec class, agr type, spa typing, PFGE and MLST. Results: PFGE and MLST revealed that all isolates were clonal and belonged to the Clonal Complex 5 (CC5). They harboured the SCC mec V and the agr II and the spa type was t6065. The majority of isolates were resistant to cefoxitin (32, 100%), penicillin (32, 100%), ampicillin (32, 100%), enrofloxacin (32, 100%), ciprofloxacin (32, 100%), fusidic acid (32, 100%), gentamicin (32, 100%), kanamycin (32, 100%), trimethoprim (32, 100%), and erythromycin (30, 93.7%). The main genes encoding antibiotic resistance were: blaZ (31, 96.8%), ermC (30, 93.7%), aph(3')-III a (3, 9.4%), aac6-aph2 (32, 100%), InuA (3, 9.4%), tetM (3, 9.4%), tetL (3, 9.4%), dfrG (28, 87.5%), fusC (32, 100%). All isolates were PVL negative; however, exfoliative-encoding genes (eta: 25) and enterotxin genes (seb: 32, seo: 32, sei: 32, ser: 32, seu: 32, seg: 32, sej: 32, sed: 31, sen: 29, seh: 26, sec: 26, sea: 6, sek: 5), haemolysin (hla (32), hld (32), hlg (32)) and immune evasion cluster proteins (scn: 32, sak: 32) were relevant. Conclusion: To the best of our knowledge this is the first report of a specific clonal spread of a multi-drug resistant MRSA-CC5- SCC mec V in a Libyan Hospital.